Eye-Tracking in Interpreting Studies: A Review of Four Decades of Empirical Studies - Hu, Ting; Wang, Xinyu; Xu, Haiming (Frontiers in Psychology, 2022)
It has been four decades since eye-tracking was first used in interpreting studies, and recent years has witnessed a growing interest in the application of this method, which holds great potential for offering a look into the “black box” of interpreting processing. However, little attention has been paid to comprehensively illustrating what has been done, what can be done, and what needs to be done with this method in this discipline. With this in view, this paper sets out to understand contributions of previous studies—key themes discussed, eye-tracking measures used, their limitations and implications, and future directions. To this end, we conduct a review of a total of 26 empirical papers from peer-reviewed journals within a time span of 4 decades ranging from 1981 to 2021. This study, as the first attempt of its kind at a comprehensive review on using eye-tracking in interpreting studies, should have implications for researchers, educators, and practitioners.